What Are The Venezuelan Poor People Like? Venezuelan CEOs View Point: Discovery Service para Universidad ICESI (2008)
Present research paper work explores low-income consumers (LIC) from Venezuelan CEOs point of view. CEOs interested in developing business or taking initiatives in the majority markets (MM). To such end, and based on the interpretative frame given by the social attribution theories and through qualitative research with analytic strategy of content, sixty six (66) response protocols from businessmen and business directors who were asked to graphically represent and describe MM consumers with respect to their personal characteristics, environment and day-to-day, were analyzed. The perception findings results tend to be negative, similar to the "individualist" category. This generates executives and managers' adverse attitudes and behaviors towards these markets where threaten are more visualized than opportunities. Therefore, a global comprehension to incorporate the socio-cultural environment is suggested as the etnomarketing perspective does. Key words: low-income consumers, majority markets, business executives, etnomarketing, and attribution theory